Climate change is predicted to alter the current pest status of Globodera pallida and G. rostochiensis in the United Kingdom. (30th March 2017) - Jones, Laura M.; Koehler, Ann‐Kristin; Trnka, Mirek; Balek, Jan; Challinor, Andrew J.; Atkinson, Howard J.; Urwin, Peter E.
Abstract: The potato cyst nematodes Globodera pallida and G. rostochiensis are economically important plant pathogens causing losses to UK potato harvests estimated at £50 m/ year. Implications of climate change on their future pest status have not been fully considered. Here, we report growth of female G. pallida and G. rostochiensis over the range 15 to 25°C. Females per plant and their fecundity declined progressively with temperatures above 17.5°C for G. pallida, whilst females per plant were optimal between 17.5 and 22.5°C for G. rostochiensis . Relative reproductive success with temperature was confirmed on two potato cultivars infected with either species at 15, 22.5 and 25°C. The reduced reproductive success of G. pallida at 22.5°C relative to 15°C was also recorded for a further seven host cultivars studied. The differences in optimal temperatures for reproductive success may relate to known differences in the altitude of their regions of origin in the Andes. Exposure of G. pallida to a diurnal temperature stress for one week during female growth significantly suppressed subsequent growth for one week at 17.5°C but had no effect on G. rostochiensis . However, after two weeks of recovery, female size was not significantly different from that for the control treatment. Future soil temperatures were simulated for medium‐ and high‐emission scenarios and combined with nematode growth data to project future implications of climate change for the two species. Increased soil temperatures associated with climate change may reduce the pest status of G. pallida but benefit G. rostochiensis especially in the southern United Kingdom. We conclude that plant breeders may be able to exploit the thermal limits of G. pallida by developing potato cultivars able to grow under future warm summer conditions. Existing widely deployed resistance to G. rostochiensis is an important characteristic to retain for new potato cultivars. Abstract : The potato cyst nematodes Globodera pallida and G. rostochiensis are economically important plant pathogens causing losses to UK potato harvests estimated at £50 m/year. These nematodes are potato's main pests and alien species introduced to many potato‐growing countries from different altitudes in the Andes. Implications of climate change on their future pest status have not been fully considered. Here, we combine nematode growth data collected from the glasshouse with future soil temperatures simulated for medium‐ and high‐emission scenarios to project future implications of climate change for the two species. For the first time, we establish soil temperatures associated with climate change may reduce G. pallida 's pest status in southern United Kingdom but not the more readily controlled G. rostochiensis . Breeding potato plants suited to future warm conditions that suppress G. pallida would offset its currently inadequate control by resistant cultivars.